Macrominerals and Trace Element Requirements for Beef Cattle. - Luiz Fernando Costa e Silva; Sebastião de Campos Valadares Filho; Terry Eugene Engle; Polyana Pizzi Rotta; Marcos Inácio Marcondes; Flávia Adriane Sales Silva; Edilane Costa Martins; Arnaldo Taishi Tokunaga (PLoS ONE)
Eighty-seven Nellore animals were utilized in this study to estimate net requirements for the maintenance and growth of beef cattle as well as the retention coefficients of 13 minerals: macrominerals (Ca, P, Mg, K, Na, and S) and trace elements (Cu, Fe, Mn, Se, Zn, Co, and Cr). The net requirements for maintenance and the true retention coefficient were estimated by using the regression between apparent retention and intake for each mineral. The net requirement for maintenance (μg/kg BW) and retention coefficients (%) were 163 and 85 for Cu, 2,097 and 53 for Fe, 32.3 and 24 for Mn, 3.72 and 48 for Se, 669 and 0.80 for Zn, 18.4 and 86 for Co, and 22.9 and 78 for Cr. The dietary requirements of macrominerals (g/kg DMI) were 5.12 for Ca, 2.38 for P, 0.96 for Mg, 2.40 for K, 0.79 for Na, and 1.47 for S. This is the first study using Nellore cattle to estimate mineral requirements; considering that Nellore cattle are the most common breed in Brazil and that Brazil is a major beef producer globally, this knowledge can help producers to improve animal performance by supplying the correct amount of minerals.